2011
DOI: 10.1111/j.1467-971x.2011.01716.x
|View full text |Cite
|
Sign up to set email alerts
|

English teacher preference: the case of China's non‐English‐major students

Abstract: In an era when English has become the uncontested world language, this study explores who Chinese non-English majors prefer as their English teachers: English teachers from China (ETCs) or so-called native-speaking English teachers (NETs). This issue has been keenly debated in the Chinese press in recent years. However, it is not a debate in which the voices of the learners and teachers of English have been sufficiently reported through empirical studies. The study draws comprehensive data from 984 college stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…The second implication is to urge the reconceptualization of ideal English teachers understanding among NNESTs. It is important for the local teachers to be confident with themselves and understand that they are not inferior to native teachers (He & Miller, 2011;Kontra, 2000). The fact that each group has its own advantages and disadvantages for being native and non-native, both NESTs and NNESTs are actually on the same level, so what remains is the endeavour to upgrade what is missing.…”
Section: Discussionmentioning
confidence: 99%
“…The second implication is to urge the reconceptualization of ideal English teachers understanding among NNESTs. It is important for the local teachers to be confident with themselves and understand that they are not inferior to native teachers (He & Miller, 2011;Kontra, 2000). The fact that each group has its own advantages and disadvantages for being native and non-native, both NESTs and NNESTs are actually on the same level, so what remains is the endeavour to upgrade what is missing.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the Chinese learners and teachers of college English all prefer the NS model in their English classroom (He and Li 2009;He and Zhang 2010;Kirkpatrick and Xu 2002). The English teachers that Chinese learners most welcome are either qualified NS teachers or local teachers with training experience in Englishspeaking countries (He and Miller 2011). An interview study of Chinese students who volunteered in the Olympic Games, Beijing, in 2008 revealed that, despite their extensive experience of ELF through their interactions with nonnative speakers of the language, they preferred American English and British English to that of other users of English before and after participating in the Olympic Games (Lin and Gao 2010).…”
Section: English Language Teaching In Chinamentioning
confidence: 97%
“…Rong ; Li ; Gu & Xiang ; Du & Jiang ; Jiang ; Wei & Fei ); (2) Chinese speakers’ perceptions and attitudes towards the variety (e.g. Hu ; Chen & Hu ; He & Li ; He & Miller ); (3) the role of English in China's language curriculum (e.g. Bianco et al.…”
Section: Research On Lexicogrammar In World Englishesmentioning
confidence: 99%